Delay-throughput and buffer utilization characteristics of some statistical multiplexers - Karim, M.R. (1987)
This paper presents the delay-throughput and buffer utilization characteristics of a few statistical multiplexers. Two of the various schemes that may be used to access the multiplexer are considered: the point-to-point access scheme where the traffic is carried between each user and the multiplexer over a separate link in a star topology, and the carrier sense multiple access protocol with collision detection (CSMA/CD) that is used over a shared communication link. Results from computer simulations show that for the n multiplied by 1 statistical multiplexer using the star topology, the delay and buffer size utilized increase exponentially with the channel utilization factor rho . The delay-throughput characteristics of a well designed multiplexer using the CSMA/CD access protocol are comparable to those of the n multiplied by 1 multiplexer based on the star topology. With the CSMA/CD protocol, as the packet size is increased, the delay normalized to the packet size, while a function of rho , first decreases and eventually tends to a limit.